El concepto de simbiosis desde la relación entre hongos formadores de micorrizas y raíces de las plantas: estrategia teórico práctica para grado quinto (2020)
This paper identified the ideas and conceptions of fifth-grade students on microorganisms, plant parts and relationships in ecosystems, to design and implement didactic sequences, supported by the pedagogical model of action research. The proposal was developed with students from the school La Palestina I.E.D., from the town of Engativá in the city of Bogotá, Colombia. Four teaching sequences were proposed, each with opening, development and closing activities, which included tasks in the classroom, laboratory and/or field, as well as home sessions with the support of parents. A test was performed with carrot, parsley, chamomile and marigold seedlings, which were inoculated with commercial mycorrhizae and other seedlings of the same species that were used as control. The students followed the seedlings and were able to determine that the symbiotic relationship between the mycorrhizae and the roots of the seedlings was beneficial for all the species worked, examining variables such as number of total leaves, total length of seedling, fresh weight and dry weight. Finally, the roots inoculated with mycorrhizae were stained and microscopically observed. In this way, children changed the negative conception of micro-organisms and began to relate them to processes of vital importance in ecosystems, while understanding the concept of symbiosis in a significant way.